The Analysis of The Influence of Ethical Communication and Patient Trust on The Decision to Reuse Dialysis Services - Marsha Vania; Purwanti Aminingsih; Enrico Adhitya Rinaldi (CV. Inara, 2026)
Chronic kidney disease (CKD) is a global health problem with increasing prevalence, making haemodialysis a critical service in hospitals. Patients' decisions to reuse dialysis services are influenced not only by medical factors, but also by ethical communication between healthcare professionals and patient trust. This study aims to analyse the influence of ethical communication and patient trust on the decision to reuse dialysis services at Dr. Dradjat Prawiranegara Regional General Hospital, Serang, Indonesia. The study used a quantitative approach with a survey of 133 active haemodialysis patients. Instrument validity was tested using Confirmatory Factor Analysis (CFA) with a loading factor >0.5 and Cronbach's Alpha reliability >0.7. Data analysis was performed using Structural Equation Modelling (SEM) using AMOS. The results of the study proved that ethical communication had a positive and significant effect on patient trust (CR = 7.669; p = 0.000), patient trust had a significant effect on the decision to reuse dialysis services (CR = 6.388; p = 0.000), and patient trust was proven to be a mediating variable that strengthened the influence of ethical communication on patient decisions (indirect effect = 0.476). This study emphasized the importance of integrating ethical communication and strengthening patient trust as a managerial strategy to improve service quality and support the sustainability of dialysis services.